Psychological Support as a Factor of the Training Process Quality Improvement - Kosendiak, Jan; Ptak, Ewelina (Journal of Education, Health and Sport, 2017)
Supportive activities may be one of the ways of the training process optimization. Support involves both components of the training process, i.e. training and rest. The training support is aimed at the training load increase or at such orientation of the adaptation processes to meet the training goals as closely as possible. The different aims lay behind the methods that support the rest mechanisms. It is about increasing the peace of the regeneration and recovery processes. This term describes all activities aimed at restoring the full exercise capacity of the athlete after work. The psychological support of the training process can be one of the ways to minimize training disturbances and it should therefore be an essential part of the training process management in case of the top ranked athletes. To improve the psychological support system of the training process and to improve the system quality, it is necessary to analyze the current situation. That’s why, authors of the paper decided to ask the members of the Polish Olympic team competed at the 2016 Olympic Games in Rio de Janeiro on types of relaxation techniques they accepted and used before the competition. The relaxation techniques were deliberately limited to the pre-start relaxation techniques as the study was treated as a pilot study dedicated to the problem identification. Therefore, the authors of the paper formulated its aim, as the identification of the pre-start relaxation preferences of the Olympic team members. The following research questions were formulated to meet the aim of the study: • What types of the pre-start relaxation techniques are declared and accepted by the Olympians? • Could the preferred pre-start relaxation techniques be considered rational, planned, and consciously implemented? A written interview with an online questionnaire was used as a research method. The study was conducted before the 2016 Olympic Games in Rio de Janeiro, among the representatives of Poland qualified for the Games. The questionnaire consisted of demographics and 10 questions answered by the respondents in accordance with the scale: Strongly disagree, Disagree, Neither agree nor disagree, Agree, and Strongly agree. The survey was voluntary and completely anonymous. The study involved 54 participants of the 2016 Olympic Games in Rio de Janeiro. 25 of them were men, and 29 were women. The 43 athletes had the International Champion title, while the remaining 11 athletic had the Champion title. The average age of the respondents was 27 years and 5 months (min 19 years, max 38 years), and the training period amounted to 13 years and 5 months on average (minimum 5 years, maximum 24 years). The research results show the following: • Most of the investigated Olympians know and apply visualization training as a pre-start relaxation technique, • Over 70% of them accept and apply music during pre-start relaxation, • The Olympians are very appreciative of meeting friends before the start, • As many as 70% of respondents do not accept or use computer games, • The subjects use also physiotherapy as a relaxation technique, • Three people admitted they accept alcohol as a pre-start relaxation technique. Generally speaking, preferred behaviors seem to be accidental, unplanned, and uncontrolled. Therefore, it is recommended that both the pre-start relaxation and all psychological support activities are strictly planned in accordance with executed training objectives, accurately implemented throughout the training cycle, and controlled, as in case of training loads.